2016
DOI: 10.1080/19420862.2016.1158370
|View full text |Cite
|
Sign up to set email alerts
|

Length-independent structural similarities enrich the antibody CDR canonical class model

Abstract: Complementarity-determining regions (CDRs) are antibody loops that make up the antigen binding site. Here, we show that all CDR types have structurally similar loops of different lengths. Based on these findings, we created length-independent canonical classes for the non-H3 CDRs. Our length variable structural clusters show strong sequence patterns suggesting either that they evolved from the same original structure or result from some form of convergence. We find that our length-independent method not only c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
105
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
2

Relationship

5
4

Authors

Journals

citations
Cited by 49 publications
(111 citation statements)
references
References 54 publications
6
105
0
Order By: Relevance
“…For example, ten-residue H1 loops, eleven-residue H1 loops, and eleven-residue L1 loops are separate BLAST-formatted databases. This ensures a compatible canonical conformation is chosen for each CDR, although recently others have had success using different length loop templates, particularly when somatic hypermutation introduces indels 26 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, ten-residue H1 loops, eleven-residue H1 loops, and eleven-residue L1 loops are separate BLAST-formatted databases. This ensures a compatible canonical conformation is chosen for each CDR, although recently others have had success using different length loop templates, particularly when somatic hypermutation introduces indels 26 .…”
Section: Introductionmentioning
confidence: 99%
“…PIGS does not include backbone refinement, and as a result it returns structures very rapidly with minimal computational cost. ABodyBuilder includes extensive refinement and has recent developments 49 ; it is different in that it allows CDR templates of mismatched lengths 26 and exploits a full six-dimensional V L -V H determination strategy 7 . RosettaAntibody is unique in that its extensive conformational refinement focused in antibody degrees of freedom is designed and tested toward creating a structure that is at an energy minimum and appropriate for downstream applications including docking or design.…”
Section: Introductionmentioning
confidence: 99%
“…This is important, since it has been shown that loops of different lengths can adopt similar conformations (Nowak et al , 2016), and other methods do not make use of this information. Sphinx is capable of generating high-quality decoy sets that are enriched with near-native conformations and in addition produces more accurate predictions than can be achieved using a straightforward ab initio algorithm.…”
Section: Discussionmentioning
confidence: 99%
“…A length-independent canonical form clustering protocol (36) was run on the North-defined (37) CDR loops of a SAbDab (35) snapshot from 26th September 2017. Model loops were inferred to have identical canonical forms to the template used by ABodyBuilder (19).…”
Section: Canonical Formsmentioning
confidence: 99%